PENGARUH KARAKTERISTIK DEWAN KOMISARIS, STRUKTUR KEPEMILIKAN, DAN AGRESIVITAS PAJAK PADA REAKSI PASAR - Sri Sundari, Ni Made Sanca; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
This study aimed to determine the factors that influence the market reaction when publishing the annual financial statements. Factors that were analyzed are the sized of the board of commissioners, the board of commissioners independent, and women commissioners as a proxy for characteristic of commissioner; managerial, institutional, and public ownership as a proxy for ownership structure; and the effective tax rate (ETR) as a proxy for tax aggressiveness. This study used the companies Property, Real Estate, and Building Construction which is listed in Indonesian Stock Exchange in 2010-2013 as the sample were selected by purposive sampling and analyzed with multiple linear regressions analysis. The result of the analysis showed that the size of the board of commissioners, the board of commissioners independent, managerial ownership, institutional and public did not affect the market reaction while women commissioners and tax aggressiveness had a positive influence on market reaction.
Keywords: market reaction, the board of commissioners, ownership structure, tax aggressiveness